Intervensi Non Farmakologi dalam Penanganan Konstipasi pada Pasien Stroke - Kristiowati, Suli; Soesanto, Edy; Pohan, Vivi Yosafianti (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
In stroke, disruption of the relationship between the nervous and digestive systems due to blockage of blood vessels in the brain by a thrombus or embolus can result in constipation. Constipation that is not managed effectively will affect the quality of life. Handling of constipation problems in stroke patients can be done with non-pharmacological therapy that does not cause side effects. The purpose of this study was to determine non-pharmacological therapy for treating constipation in stroke patients. This study was a systematic literature review. The source of literature was the database on the app.dimensions.ai website. The literature search was conducted in April 2024, using the keywords "Non-pharmacological interventions for treating constipation in stroke patients". The flowchart used was the Preferred Reporting Items for Systematic Review and Meta-Analysis. The search obtained 66,642 articles published in 2020-2024, in English and Indonesian, then filtered down to 8 articles. The review results show that non-pharmacological therapies for constipation in stroke patients are acupressure, abdominal massage, acupuncture, visceral mobilization and digital rectal stimulation. These therapies had been proven effective in relieving constipation, improving distension, increasing bowel movements, maintaining static balance and preventing neurogenic bowel dysfunction in stroke patients. Furthermore, it was concluded that various non-pharmacological therapies are effective in treating constipation in stroke patients, with their respective mechanisms.Keywords: stroke; constipation; non-pharmacological therapy ABSTRAK Pada stroke, gangguan hubungan antara sistem saraf dan pencernaan akibat penyumbatan pembuluh darah otak oleh trombus atau embolus dapat mengakibatkan konstipasi. Konstipasi yang tidak dikelola secara efektif akan mempengaruhi kualitas hidup. Penanganan masalah konstipasi pada pasien stroke dapat dilakukan dengan terapi non farmakologi yang tidak menimbulkan efek samping. Tujuan dari studi ini adalah mengetahui terapi non farmakologi untuk penanganan konstipasi pada pasien stroke. Studi ini merupakan systematic literature review. Sumber literatur adalah database pada website app.dimensions.ai. Pencarian literatur dilakukan pada bulan April 2024, menggunakan kata kunci “Non-pharmacological interventions for treating constipation in stroke patients”. Diagram alir yang digunakan adalah Preferred Reporting Items for Systematic Review and Meta-Analysis. Pencarian mendapatkan 66.642 artikel terbitan tahun 2020-2024, berbahasa Inggris dan Indonesia, lalu disaring hingga tinggal 8 artikel. Hasil review menunjukkan bahwa terapi non-farmakologi untuk konstipasi pada pasien stroke adalah akupresur, pijat perut, akupuntur, mobilisasi viseral dan digital rectal stimulation. Terapi-terapi ini terbukti efektif meringankan konstipasi, memperbaiki distensi, meningkatkan pergerakan usus, menjaga keseimbangan statis serta mencegah disfungsi usus neurogenik pada pasien stroke. Selanjutnya disimpulkan bahwa berbagai terapi non-farmakologi efektif untuk menangani konstipasi yang terjadi pada pasien dengan stroke, dengan mekanisme masing-masing.Kata kunci: stroke; konstipasi; terapi non-farmakologi